Pengaruh Aspek Partisipasi dan Transparansi Terhadap Kinerja Melalui Penegakan Disiplin Di Dinas Perikanan Kabupaten Probolinggo - Syarifuddin Abbas (Jurnal Ekonomi dan Manajemen, 2018)
Performance is a process of measuring employee performance based on predetermined rules, by comparing the objectives with the job description requirements that is the standard work that has been established during a certain period. Discipline in an organization is an important problem faced in carrying out the job duties of each employee. This study aims to analyze the influence of participation on discipline, analyze the influence of transparency on the discipline, analyze the influence of participation on performance, analyze the effect of transparency on performance, analyze the influence of discipline on performance, analyze the influence of participation on performance through discipline, and analyze the influence of transparency to performance through discipline The results show that discipline is the amplifier (mediate) participation on employee performance. The higher the employee participation the discipline will increase. Performance of employees will be increased if employees discipline in completing the work. Discipline is able to mediate the effect of transparency on the performance of employees, which means that transparency can improve employee performance if the employee is disciplined in completing the job.